Kepemimpinan sebagai Hamba: Kajian Teologis Matius 20: 20-28 dan Relevansinya bagi Kepemimpinan Pendeta Gereja Kristen Protestan Pakpak Dairi (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the concept of servant leadership based on Matthew 20:20-28 and its relevance to the leadership of pastors in the Pakpak Dairi Protestant Christian Church (GKPPD). The background of this research stems from the dynamics of church leadership, which still faces challenges in realizing the values of service, humility, and relational closeness as taught by Jesus Christ. This research uses a qualitative method with a literature review approach, focusing on the analysis of biblical texts and literature on biblical theology, Christian leadership, and pastoral spirituality. The results of the study show that Jesus introduced a leadership paradigm that is different from the world's pattern, namely leadership that is rooted in service, sacrifice, and love. This principle requires spiritual transformation in church leaders so that their ministry reflects the character of Christ. In the context of GKPPD, the application of servant leadership is important because of the influence of local culture, which emphasizes social structure, and the congregation's need for authentic, relational, and humble leaders. This research confirms that servant leadership is not only theological but also contextual in responding to the challenges of church life, as well as providing theoretical and practical contributions in building a leadership paradigm that is in line with the Gospel and relevant to the local church today.